Experimental and calculated terahertz spectra of naphthalene and 1,4-dihydroxynaphthalene in the 0.5 - 6 terahertz region - Ponseca, C. J. S. (Animo Repository, 2008)
Far infrared (IR) spectra of naphthalene and 1,4-dihydroxynaphthalene (1,4-naphthol) were measured in the region from 0.5 to 6.3 THz at room temperature using a GaP THz wave generator. Quantum chemical calculations were performed to obtain normal mode coordinates and frequencies for an isolated molecule case of naphthalene and 1,4-naphthol. © 2008 IOP Publishing Ltd.